KAJIAN LITERATUR PENGARUH COOPERATIVE LEARNING TERHADAP HASIL BELAJAR IPS MATERI KEGIATAN EKONOMI KELAS V SEKOLAH DASAR - Ainur Rasikin, Muhammad; Anam Wijaya, Fahriz; Nur Rohmah, Eva; Mega Kalista, Zulfia; Tri Febrianto, Priyono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the influence of cooperative learning on students' social studies learning outcomes, particularly in the economic activities material for fifth-grade elementary school students. This research is motivated by the relatively low learning outcomes in social studies, especially in understanding economic concepts, which are often caused by the dominance of teacher-centered instructional approaches. This study applies a literature review method by examining and synthesizing relevant research findings from journals, articles, and scientific publications related to cooperative learning implementation in elementary education. Data were collected through documentation techniques and analyzed systematically from selected literature sources. The findings reveal that the application of cooperative learning contributes positively to improving students' learning outcomes in social studies, especially in economic activities material. Cooperative learning promotes active student involvement, enhances collaboration and communication skills, encourages critical thinking, and strengthens conceptual understanding through group interaction and discussion. In addition, the implementation of cooperative learning increases students’ motivation and engagement during the learning process. Therefore, cooperative learning is considered an effective instructional approach to improve social studies learning outcomes in economic activities material for fifth-grade elementary school students.